Phytochemical studies of Helichrysum patulum - Swartz, Vuyiswa Gladys (University of the Western Cape, 2013)
Magister Scientiae - MSc === Since Helichrysum is known by the indigenous people of Africa for therapeutic properties, such as against colds, flu and wounds, the aim of this study was to focus on the patulum species found predominantly in the Western Cape region of South Africa and by means of isolation and identification of the plant constituents, be able to relate the therapeutic activity on the basis of literature precedents, to the compounds extracted. === South Africa